An extended multi-objective capacitated transportation problem with mixed constraints in fuzzy environment. (21st February 2020) - Gupta, Srikant; Ali, Irfan; Ahmed, Aquil
In this paper, we study a multi-objective capacitated transportation problem (MOCTP) with mixed constraints. This paper is comprised of the modelling and optimisation of an MOCTP in a fuzzy environment in which some goals are fractional and some are linear. In real life application of the fuzzy goal programming (FGP) problem with multiple objectives, it is difficult for the decision maker(s) to determine the goal value of each objective precisely as the goal values are imprecise or uncertain. Also, we developed the concept of linearisation of fractional goal for solving the MOCTP. In this paper imprecision of the parameter is handled by the concept of fuzzy set theory by considering these parameters as a trapezoidal fuzzy number. α -cut approach is used to get the crisp value of the parameters. Numerical examples are used to illustrate the method for solving MOCTP.